SERUM CREATINE PHOSPHOKINASE ACTIVITY IN RABBITS DURING REGENERATION OF EXPERIMENTALLY DAMAGED MUSCLE TISSUE AND AFTER ITS STIMULATION BY TRANSPLANTED MSC - N. V. STADNYK; Roman Bokotko; T. L. SAVCHUK; Mariia Kulida; Anatolii Mazurkevych (Ukrainian Journal of Veterinary Sciences, 2021)
According to statistics, in modern veterinary practice, the percentage of muscle injuries among sport and working animals ranges from 40–70% of sports injuries. Quite often there are cases with muscle injuries of skeletal muscles, namely extremities. This scientific work describes the research methodology, stages of research step-by-step, and studies the relationship of dynamics of the activity of a single biochemical blood indicator. The essence of the method was to model the injury of muscle tissue performed by the skin and fascia dissection and cutting off in the area of the midplane of the pelvic head of the biceps femoris muscle, measuring 1.5×1.5 cm to a depth of 1.5 cm of muscle tissue in 105 laboratory animals, divided into 4 groups with the use of various treatment methods. We analyze the results of one of the most effective biochemical methods for diagnosing damage of muscle fibers in the skeletal system and compare the activity of the creatine phosphokinase iso-enzyme depending on the stage of the study. Other research methods such as clinical, biochemical, ultrasonographic, and histological were recorded on 4, 7, 10, 14, 21, and 28 days. We analyzed the latest literature sources and concluded that on the 4th and 7th days, the level of creatine phosphokinase in the groups with intravenous and intramuscular administration of allogeneic mesenchymal stem cells is higher than the reference values but significantly lower compared to the control groups and the traditional method of treatment. But we observe a significant decrease in serum creatine phosphokinase levels 2 times in rabbits on the 10th day in the intravenous administration group compared with the control group of animals and in 1.6 times compared with traditional treatment. The group of animals with intramuscular administration has reference values on the 14th day, compared with the control in 1.3 times lower, traditional treatment in 1.2 times. And on the 21st day, we get reference values for a group of animals with traditional treatment. The level of creatine phosphokinase activity decreases in the control group of animals on the 28th day of the research, which indicates a complete muscle rupture. The results of studies showed that the highest activity of the creatine phosphokinase enzyme during the study was shown by groups of animals with control and traditional treatment, which indicated significant structural, functional, and destructive disorders of the muscle fibers of skeletal tissues with severe trauma. Thus, it is noted that the activity of the enzyme in conditions of damage of skeletal muscle tends to increase in accordance with the severity of the injury.